Rural Entertainment in the Püspökladány sub-region - Tikász, Edit Ildikó (Acta Agraria Debreceniensis, 2006)
The Püspökladány statistical sub-region is geographically located in Hajdú-Bihar county’s south-west corner, in the area called Nagy-Sárrét. The tourism of the sub-region has been highly determined by the proximity of Hortobágy National Park and the presence of thermal water, one of the most important resources of the region. As Hajdú-Bihar county – especially Debrecen, Hajdúszoboszló and Hortobágy – possesses these attractive factors as well, in the Püspökladány sub-region rural tourism could be an important means of catching the interests of – mostly Hungarian – tourists.In the course of this research, my objectives were to introduce the rural hosts of the sub-region, the main features and problems of rural hospitality as an enterprise and the characteristics and activities of rural tourist – from the view of the hosts.I chose questionnaires as the method of the investigation, and evaluated them with the help of SPSS and Microsoft Excel software. During the evaluation, I calculated distribution, arithmetic mean, deviation and carried out significance-analysis.The investigations confirmed my presumption, i.e. rural tourism has not gained ground yet in the Püspökladány sub-region. This statement is proved by the fact that I completed only 8 questionnaires in a sub-region with 13 settlements, where rural host activity concentrates on 3 settlements. The results of the questionnaire-evaluation prove the aforesaid.